2016
DOI: 10.3389/fmicb.2016.01101
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Microbial Community under Drying and Rewetting Cycles of Three Forest Soils

Abstract: Forest soil ecosystems are associated with large pools and fluxes of carbon (C) and nitrogen (N), which could be strongly affected by variation in rainfall events under current climate change. Understanding how dry and wet cycle events might influence the metabolic state of indigenous soil microbes is crucial for predicting forest soil responses to environmental change. We used 454 pyrosequencing and quantitative PCR to address how present (DNA-based) and potentially active (RNA-based) soil bacterial communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 60 publications
6
13
0
Order By: Relevance
“…community, genomes and genes. Our findings support that there is a distinct community shift upon soil drying which is consistent with previous studies (Zhou et al 2016;Pajares et al 2018). Besides the confirmation that there are clear impacts on the community as a whole, we also noticed that new members of bacterial populations being more abundant in both conditions (dry and wet), which were not previously reported in a single study and/or similar soil profile(s).…”
Section: Resultssupporting
confidence: 92%
“…community, genomes and genes. Our findings support that there is a distinct community shift upon soil drying which is consistent with previous studies (Zhou et al 2016;Pajares et al 2018). Besides the confirmation that there are clear impacts on the community as a whole, we also noticed that new members of bacterial populations being more abundant in both conditions (dry and wet), which were not previously reported in a single study and/or similar soil profile(s).…”
Section: Resultssupporting
confidence: 92%
“…Our results shown, that Actinobacteria increased in relative abundance with desiccation. This results is agrees with the response of bacterial communities in California grassland soil study [55] and the results obtained by [47] [56] who shown that this phylum were one of the most responsive to change in water availability; increased with dry-down and decreased with wet-up.…”
Section: Resultssupporting
confidence: 92%
“…Many studies have suggested that bacterial communities are highly capable of recovery after specific disturbance, such as drying-wetting cycle, warming-cooling cycle and lake mixing [ 11 , 38 , 58 , 59 ]. Thus, it is important to reconcile the two seemingly contradictory results.…”
Section: Discussionmentioning
confidence: 99%